Long‐term outcomes after randomization to buprenorphine/naloxone versus methadone in a multi‐site trial. (13th January 2016) - Hser, Yih‐Ing; Evans, Elizabeth; Huang, David; Weiss, Robert; Saxon, Andrew; Carroll, Kathleen M.; Woody, George; Liu, David; Wakim, Paul; Matthews, Abigail G.; Hatch‐Maillette, Mary; Jelstrom, Eve; et al.
Abstract: Aims: To compare long‐term outcomes among participants randomized to buprenorphine or methadone. Design, Setting and Participants: Follow‐up was conducted in 2011–14 of 1080 opioid‐dependent participants entering seven opioid treatment programs in the United States between 2006 and 2009 and randomized (within each program) to receive open‐label buprenorphine/naloxone or methadone for up to 24 weeks; 795 participants completed in‐person interviews ( 74% follow‐up interview rate) covering on average 4.5 years. Measurements: Outcomes were indicated by mortality and opioid use. Covariates included demographics, site, cocaine use and treatment experiences. Findings: Mortality was not different between the two randomized conditions, with 23 (3.6%) of 630 participants randomized to buprenorphine having died versus 26 (5.8%) of 450 participants randomized to methadone. Opioid use at follow‐up was higher among participants randomized to buprenorphine relative to methadone [42.8 versus 31.7% positive opioid urine specimens, P < 0.01, effect size (h) = 0.23 (0.09, 0.38); 5.8 days versus 4.4 days of past 30‐day heroin use, P < 0.05, effect size (d) = 0.14 (0.00, 0.28)]. Opioid use during the follow‐up period by randomization condition was also significant ( F (7, 39 600) = 3.16; P < 0.001) due mainly to less treatment participation among participants randomized to buprenorphine than methadone. Less opioid use was associated with both buprenorphine and methadone treatment (relative to no treatment); no difference was found between the two treatments. Individuals who are white or used cocaine at baseline responded better to methadone than to buprenorphine. Conclusions: There are few differences in long‐term outcomes between buprenorphine and methadone treatment for opioid dependence, and treatment with each medication is associated with a strong reduction in opioid use.